1997
DOI: 10.1046/j.1365-2362.1997.2220763.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of nitric oxide to exercise‐induced changes in healthy volunteers: effects of acute exercise and long‐term physical training

Abstract: Endothelium plays a central role in the regulation of regional blood flow through the release of certain vasoactive substances. We conducted this study to test whether an increase in the production of nitric oxide (NO) metabolites, atrial natriuretic peptide (ANP) and plasma and intraplatelet cyclic guanosine 3':5' monophosphate (cGMP) is involved in the adaptation to chronic exercise in physically trained people and in the vasodilatation induced by acute physical exercise. We studied one group of 10 trained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
48
1
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 28 publications
8
48
1
2
Order By: Relevance
“…It is in accordance with numerous previous studies that showed that regular physical activity increases the bioavailability of • NO Jungersten et al, 1997;Maeda et al, 2001;Maiorana et al, 2003) and that physically active people have greater basal • NO production compared with a sedentary population (Green et al, 2004;Poveda et al, 1997;Banfi et al, 2006). Studies that investigated the effects of acute exercise on • NO production yielded various results.…”
Section: Comparison Of Blood Pro/antioxidant Levels Before and After supporting
confidence: 91%
See 1 more Smart Citation
“…It is in accordance with numerous previous studies that showed that regular physical activity increases the bioavailability of • NO Jungersten et al, 1997;Maeda et al, 2001;Maiorana et al, 2003) and that physically active people have greater basal • NO production compared with a sedentary population (Green et al, 2004;Poveda et al, 1997;Banfi et al, 2006). Studies that investigated the effects of acute exercise on • NO production yielded various results.…”
Section: Comparison Of Blood Pro/antioxidant Levels Before and After supporting
confidence: 91%
“…Studies that investigated the effects of acute exercise on • NO production yielded various results. Some studies reported • NO increase with exercise, some reported no change in • NO production and some reported a decrease in • NO production with exercise (Jungersten et al, 1997;Rassaf et al, 2007;Allen et al, 2006;Allen et al, 2009;Djordjevic et al, 2010a;Poveda et al, 1997;Djordjevic et al, 2010b;Jakovljevic et al, 2011;Cubrilo et al, 2011). Those differences are probably due to different protocols, i.e.…”
Section: Comparison Of Blood Pro/antioxidant Levels Before and After mentioning
confidence: 99%
“…NO is a well-known vasodilator that plays a key role in blood supply to the tissues, including working muscles [10]. It has been demonstrated that an acute bout of exercise enhances the production of NO, and thereby contributes to skeletal muscle vasodilatation [4,21]. NO is involved in cardioprotection [20], myocardial respiration [15,16], and in insulin-independent glucose uptake into the working muscle fibres [17].…”
Section: Introductionmentioning
confidence: 99%
“…O estudo de MacDonald et al (26) , por exemplo, não encontrou associação entre os valores de peptídio atrial natriurético com a ocorrência da HPE após uma sessão de exercício com pesos. Contudo, essa substância, embora associada ao comportamento hemodinâmico, não deve apresentar isoladamente efeito relevante na redução da PA após exercício (44) . Mais recentemente, Rezk et al (24) , observaram que a redução na PA após o exercício com pesos deve-se, pelo menos em parte, à diminuição no débito cardíaco.…”
Section: Possíveis Mecanismosunclassified